Towards a New Societal Paradigm: The Components, Challenges, and Opportunities of Society 5.0 - Gülen, Salih; Dönmez, Ismail; Idil, Sahin (Sahin IDIN, 2024)
The research deals with the social evolution of mankind in the historical process and the concept of "Society 5.0", which has recently come to the fore in this evolution. Starting from hunter-gatherer society in the history of mankind, it has passed through the stages of agriculture, industry and information society, and today, with technological advances, a new phase called "Society 5.0" has been transitioned. Society 5.0 is a model of society, especially developed under the leadership of Japan, in which technologies such as artificial intelligence, big data and the Internet of Things are integrated to improve human life. The research examines in detail the reasons, elements, concerns and achievements of this new society model, while emphasising the sustainable development goals.
Keywords: Science Education; Fen Bilgisi Egitimi